2018
DOI: 10.3390/nano8110962
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Graphene/MoS2 Heterostructure: First Principles Calculations

Abstract: The electronic structure and the optical properties of Graphene/MoS2 heterostructure (GM) are studied based on density functional theory. Compared with single-layer graphene, the bandgap will be opened; however, the bandgap will be reduced significantly when compared with single-layer MoS2. Redshifts of the absorption coefficient, refractive index, and the reflectance appear in the GM system; however, blueshift is found for the energy loss spectrum. Electronic structure and optical properties of single-layer g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 45 publications
(46 reference statements)
7
26
0
Order By: Relevance
“…Within the HfS 2 layer the charge accumulation mainly occurs around the sulphur atoms, an indication that these atoms gain charges. A similar observation has been made for the Gr/MoS 2 76 and tungsten sulde (Ws 2 )/Gr, 77 heterostructures. It has also been shown that tungsten diselenide (WSe 2 ) is a weak acceptor of electrons upon contact with Gr, in a WSe 2 /Gr heterostructure.…”
Section: Charge Density Distribution and Population Analysissupporting
confidence: 83%
“…Within the HfS 2 layer the charge accumulation mainly occurs around the sulphur atoms, an indication that these atoms gain charges. A similar observation has been made for the Gr/MoS 2 76 and tungsten sulde (Ws 2 )/Gr, 77 heterostructures. It has also been shown that tungsten diselenide (WSe 2 ) is a weak acceptor of electrons upon contact with Gr, in a WSe 2 /Gr heterostructure.…”
Section: Charge Density Distribution and Population Analysissupporting
confidence: 83%
“…First principle calculations are applied to study the electronic and magnetic properties of Stone-Wales defected graphene [27] and the optical properties of graphene/MoS 2 heterostructures [28], while experimental work is carried out to investigate the properties of graphene/Si Schottky junctions [29] and to realize visible-light driven photoanodes for water oxidation [30].…”
Section: Graphene and Graphene Oxidementioning
confidence: 99%
“…First principle calculations are also applied by Qiu et al [28] to demonstrate that the electronic structure and the optical properties of graphene and monolayer molybdenum disulfide (MoS 2 ) are changed after they are combined in an heterostructure. MoS 2 [32,33] is the best known material of the transition metal dichalcogenide (TMD) family that will be treated next.…”
Section: Graphene and Graphene Oxidementioning
confidence: 99%
“…Intuitively, by combining the outstanding properties of graphene and 2D MoS 2 to form high‐performance devices with unprecedented properties is a natural research guideline. Indeed, the integration of MoS 2 and graphene has been successfully synthesized for wide range applications, such as solar cells, photodetectors, transistors, and biosensors . With the success of the discovery of many interesting novel devices based on vertical stacking, 2D nanocomposites have drawn increasing interests.…”
mentioning
confidence: 99%
“…In the second step, the carriers can go through resonant tunneling from energy levels in graphene to the near energy levels in MoS 2 quantum dots . Note the speed of graphene intraband transition and the resonant tunneling are both much faster than the rate of recombination of carriers in MoS 2 quantum dots . Thus, in the third step, more carriers can be injected to nitrogen‐bound exciton levels or defect levels in MoS 2 quantum dots, which enables to generate population inversion and lead to the possibility of stimulated emissions.…”
mentioning
confidence: 99%